Mortality and Survivors' Consumption - Michael Grimm (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In developing countries illness shocks can have a severe impact on household income. Few studies have so fare examined the effects of mortality. The major difference between illness and mortality shocks is that a death of a household member does not only induce direct costs such as medical and funeral costs and possibly a loss in income, but that also the number of consumption units in the household is reduced. Using data for Indonesia, I show that the economic costs related to the death of children and older persons seem to be fully compensated by the decrease of consumption units. In contrast, when prime-age adults die, survivors face additional costs and, in consequence, implement coping strategies. It is shown that these are quite efficient and it seems that in terms of consumption households even overcompensate their loss, although they may face a higher vulnerability in the longer term. The results suggest that the implementation of general formal safety nets can give priority to the insurance of other types of risks, such as unemployment, illness or natural disasters.
Keywords: I12; O12; J12; D12; 330; Mortality; consumption smoothing; risk; micro-model of consumption growth; Indonesia